LANDASAN PSIKOLOGI PENDIDIKAN - Yulianti , Delfita; Ilmi, Darul (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The foundation of educational psychology is a theoretical basis that involves psychological principles in the educational context. Educational psychology aims to understand the learning process and individual development so as to increase the effectiveness of the education system. This article presents an overview of several relevant foundations of educational psychology.